2019
DOI: 10.5539/ibr.v12n9p13
|View full text |Cite
|
Sign up to set email alerts
|

Linking Motivation to Employees’ Performance: the Mediation of Commitment and Moderation of Delegation Authority

Abstract: This study explores the roles of commitment and delegation authority respectively as a mediator and moderator to evaluate the impact of motivation on employee performance. A survey conducted with 180 employees as participants at OTB (Burundi Tea Office) from 4 tea factories located at Ijenda, Teza, Tora and Rwegura helped to assess the effect motivation has on employees’ performance. The correlation and regression analysis in SPSS was supported to evaluate the hypotheses of this research.  T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[15][16][17] an essential element that drives an employee to pursue organizational goals in the workplace. [18,19] JM is also an ongoing concern in organizations and is known to be a precursor/driver of overall employee performance. [20,21] An attractive incentive structure is also known to drive motivation in employees.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] an essential element that drives an employee to pursue organizational goals in the workplace. [18,19] JM is also an ongoing concern in organizations and is known to be a precursor/driver of overall employee performance. [20,21] An attractive incentive structure is also known to drive motivation in employees.…”
Section: Introductionmentioning
confidence: 99%
“…This is at variance with the expectation that suggests a positive JS level implies an improvement in JM among employees. 2,3 This is because causal relationships have been shown to exist between JS and JM in the literature. 4 The 23 The regression model as shown in Table 3 was interpreted thus; in model 1, pharmaceutical sales representatives in the motivated category, are 83% (OR=1.00-0.073) less likely to be dissatisfied with their jobs compared to those who are satisfied with their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that decreased output and productivity were linked to a lack of motivation. [1][2][3][4] JS refers to a psychological state of mind expressed as feelings of positivity and pleasure with their assessment of their jobs. 5,6 JS and JM have been used interchangeably in the literature, whereas JM is a driving force that drives the performance and execution of roles.…”
Section: Introductionmentioning
confidence: 99%
“…Participation in employee empowerment is a concept that focuses on the empowerment of each individual employee within an organization, allowing them to have a greater say in the decision-making process and allowing them to develop professionally by increasing their responsibilities and autonomy [22]. Participation in employee empowerment is important because it encourages employees to be engaged, allows their skills and talents to be maximized, and helps create a workplace atmosphere that is open to change and innovation [9,23].…”
Section: Participationmentioning
confidence: 99%